2004
DOI: 10.1099/mic.0.26761-0
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the motA gene delays the escape of the obligate predator Bdellovibrio bacteriovorus 109J from bdelloplasts of bacterial prey cells

Abstract: Bdellovibrio bacteriovorus is a Gram-negative bacterium that preys on other Gram-negative bacteria. The lifecycle of B. bacteriovorus alternates between an extracellular flagellated and highly motile non-replicative attack-phase cell and a periplasmic non-flagellated growth-phase cell. The prey bacterium containing periplasmic bdellovibrios becomes spherical but osmotically stable, forming a structure known as the bdelloplast. After completing the growth phase, newly formed bdellovibrios regain their flagellum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
(21 reference statements)
4
29
1
Order By: Relevance
“…Prey entry and flagellum-mediated movement within bdelloplasts. As we had found that contrary to the results of Flannagan and coworkers, (8), the B. bacteriovorus motAB1 strain was not significantly slower at predation during multiple rounds of infection, a single round of infection by each of the motAB1 and motAB2 strains was compared to that by the fliC1 merodiploid control by light microscopy in a "bdelloplast persistence assay." Analysis of these single rounds of infection (see Fig.…”
Section: Resultscontrasting
confidence: 48%
See 4 more Smart Citations
“…Prey entry and flagellum-mediated movement within bdelloplasts. As we had found that contrary to the results of Flannagan and coworkers, (8), the B. bacteriovorus motAB1 strain was not significantly slower at predation during multiple rounds of infection, a single round of infection by each of the motAB1 and motAB2 strains was compared to that by the fliC1 merodiploid control by light microscopy in a "bdelloplast persistence assay." Analysis of these single rounds of infection (see Fig.…”
Section: Resultscontrasting
confidence: 48%
“…In the initial annotation of each motA gene (21), they were found to encode either an extended N-terminal sequence (motA1/motA2) or a missing first transmembrane domain (motA3), but further sequence analysis revealed alternative potential start codons that rectified these issues and gave significant full-length homologies to Mot proteins of diverse other bacteria. As mentioned above MotA1 of B. bacteriovorus HD100 was a 100% identical match to the MotA of B. bacteriovorus 109J studied with antisense knockdown by Flannagan and coworkers (8). We examined the primary sequence similarities between the six Bdellovibrio MotA and MotB protein sequences in comparison to MotA and MotB from the proton-driven E. coli motor and PomA and PomB from the Vibrio alginolyticus sodium-driven motor to see if any obvious homologies suggesting a driving ion for each MotAB type could be determined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations